Post-Translational Modifications Evoked by Reactive Carbonyl Species in Ultraviolet-A-Exposed Skin: Implication in Fibroblast Senescence and Skin Photoaging - Anne Negre-Salvayre; Robert Salvayre (Antioxidants, 2022)
Photoaging is an accelerated form of aging resulting from skin exposure to ultraviolet (UV) radiation. UV-A radiation deeply penetrates the dermis and triggers the generation of reactive oxygen species (ROS) which promotes damage to DNA, lipids and proteins. Lipid peroxidation results from the oxidative attack of polyunsaturated fatty acids which generate a huge amount of lipid peroxidation products, among them reactive carbonyl species (RCS) such as α, β-unsaturated hydroxyalkenals (e.g., 4-hydroxynonenal), acrolein or malondialdehyde. These highly reactive agents form adducts on free NH2 groups and thiol residues on amino acids in proteins and can also modify DNA and phospholipids. The accumulation of RCS-adducts leads to carbonyl stress characterized by progressive cellular and tissular dysfunction, inflammation and toxicity. RCS-adducts are formed in the dermis of skin exposed to UV-A radiation. Several RCS targets have been identified in the dermis, such as collagen and elastin in the extracellular matrix, whose modification could contribute to actinic elastosis lesions. RCS-adducts may play a role in fibroblast senescence via the modification of histones, and the sirtuin SIRT1, leading to an accumulation of acetylated proteins. The cytoskeleton protein vimentin is modified by RCS, which could impair fibroblast motility. A better identification of protein modification and carbonyl stress in the dermis may help to develop new treatment approaches for preventing photoaging.